Female patients report comparable results to males after the implantation of an aragonite-based scaffold for the treatment of knee chondral and osteochondral defects: a gender-based analysis of a RCT at 4 years’ follow-up - Elizaveta Kon; Francesca De Caro; Vinod Dasa; Jason M Scopp; Berardo Di Matteo; David Flanigan; Nogah Shabshin; Sabrina Strickland; Nir Altschuler (Journal of Orthopaedics and Traumatology, 2025)
Abstract Background The aim of the study was to provide a gender-based analysis of the results of a large, multi-centre randomized controlled trial (RCT) comparing a novel cell-free aragonite-based scaffold with the standard of care (i.e. debridement/microfractures) for the treatment of chondral/osteochondral defects in knees with or without concurrent osteoarthritis. Materials and methods A total of 251 patients were included: 167 patients in the scaffold group and 84 in the control. In the scaffold group, there were 105 males and 59 females, whereas the control group consisted of 51 males and 32 females. Patients were evaluated up to 48 months after the treatment. The primary endpoint was the change from baseline to 48 months in the KOOS overall score. Treatment failures were defined as any secondary invasive intervention, including intra-articular injection or any surgery in the treated joint. All patients underwent magnetic resonance imaging (MRI) at 12 and 24 months to assess the percentage of defect fill after surgery. Results Both males and females in the scaffold group achieved significantly better results than controls in any KOOS subscale, as well as in KOOS overall, up to the final 48 months follow-up. Outcomes reported by females were non-inferior to those of males in the implant group. At 24 months’ MRI evaluation, 86.2% of male patients in the scaffold group presented at least 75% defect fill compared with 32.6% in the control group. In the scaffold group, 87.6% of female patients presented at least 75% defect fill, compared with 28% in the control group (p < 0.0001 in both cases). Responders’ rate and failure rate were also significantly better in the scaffold group for both males and females. Conclusion The aragonite scaffold outperformed the control group at 48 months’ evaluation. The gender-based analysis proved that males and females in the scaffold group presented comparable clinical and radiographical results, both significantly better than their counterparts treated by debridement/microfractures. Level of evidence: I—Randomized controlled trial. Trial registration: Clinicaltrial.gov ID: NCT03299959 (registered on 14 September 2017).